2023
DOI: 10.3390/nu15153348
|View full text |Cite
|
Sign up to set email alerts
|

Does the Micronutrient Molybdenum Have a Role in Gestational Complications and Placental Health?

Abstract: Molybdenum is an essential trace element for human health and survival, with molybdenum-containing enzymes catalysing multiple reactions in the metabolism of purines, aldehydes, and sulfur-containing amino acids. Recommended daily intakes vary globally, with molybdenum primarily sourced through the diet, and supplementation is not common. Although the benefits of molybdenum as an anti-diabetic and antioxidant inducer have been reported in the literature, there are conflicting data on the benefits of molybdenum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…Two reports found maternal urinary Mo concentrations to be positively associated with lipid peroxidation biomarkers 8-isoprostaglandin F2α (8-isoPGF2α) and the oxidative DNA damage biomarker 8-hydroxydeoxyguanosine (8-OHdG) in the third trimester (63,64) . A review reported that Mo supplementation might ameliorate the oxidative stress and reduction in antioxidant enzymes that accompanied gestational diabetes mellitus (65) . It can therefore be suggested that Sr or Mo levels rise when some kind of oxidative damage exists, and this elevation attempts in some way to restore the balance between the organism's defence and its oxidative damage and reduce the risk of SPTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two reports found maternal urinary Mo concentrations to be positively associated with lipid peroxidation biomarkers 8-isoprostaglandin F2α (8-isoPGF2α) and the oxidative DNA damage biomarker 8-hydroxydeoxyguanosine (8-OHdG) in the third trimester (63,64) . A review reported that Mo supplementation might ameliorate the oxidative stress and reduction in antioxidant enzymes that accompanied gestational diabetes mellitus (65) . It can therefore be suggested that Sr or Mo levels rise when some kind of oxidative damage exists, and this elevation attempts in some way to restore the balance between the organism's defence and its oxidative damage and reduce the risk of SPTB.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have found that Sr could suppress inflammation (68,69) . A review reported that the heightened inflammation that accompanies gestational diabetes mellitus might be ameliorated by a Mo supplementation (65) . Therefore, it is speculated that Sr and Mo could reduce the occurrence of SPTB by decreasing the inflammation during the pregnancy.…”
Section: Discussionmentioning
confidence: 99%